2018
DOI: 10.3389/fendo.2018.00435
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Morningness-Eveningness, Sleep Duration, Social Jetlag, and Body Mass Index in Asian Patients With Prediabetes

Abstract: Background: Circadian system is known to influence energy metabolism. Recent evidence suggested that evening preference could be associated with higher body mass index (BMI). Moreover, evening preference is known to be associated with insufficient sleep duration and greater social jetlag, both described to be associated with obesity. This study aimed to explore whether morningness-eveningness was directly associated with BMI or its effect was transmitted through sleep duration or social jetlag in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…The current review noted that the delay in dinner or night meals among evening chronotypes was less severe compared to shift workers (range from 19:19 to 21:31). Nonetheless, evening chronotypes remain exposed to a milder form of chronodisruption (regards irregular and delay meal timing) [77]. Thus, more studies are needed to explore whether this habit has the possibility to cause adverse long-term effects.…”
Section: Dietary Behaviourmentioning
confidence: 99%
“…The current review noted that the delay in dinner or night meals among evening chronotypes was less severe compared to shift workers (range from 19:19 to 21:31). Nonetheless, evening chronotypes remain exposed to a milder form of chronodisruption (regards irregular and delay meal timing) [77]. Thus, more studies are needed to explore whether this habit has the possibility to cause adverse long-term effects.…”
Section: Dietary Behaviourmentioning
confidence: 99%
“…An in-depth literature review in this arena also showed a lack of research in developing countries. Although there has been some research on social jetlag focusing on ethnic minorities and social jetlag (Anothaisintawee et al, 2018), there have been no significant studies conducted in the developing countries, which should be addressed in future work. However, in developing countries, such research is complicated because electronic media use can be a potential confounding factor for social jetlag.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…24 Most evidence for the role of circadian rhythms and body weight regulation is related to the timing of EI 2529 and sleep/wake cycle. 21, 23, 30–32 To date, the few studies that have assessed the association between exercise timing and weight related outcomes have been limited by study design and the lack of objective assessment methods. 2022 Due to the high levels of variability in exercise induced weight loss, further understanding the role of exercise timing could be important to maximize weight loss efforts.…”
Section: Introductionmentioning
confidence: 99%